Correlation analysis between PCR-SSCP polymorphisms of luteinizing hormone receptor gene (LHR) and reproductive traits in sheep - WANG Li-hong; GAO Qin-xue; ZHANG Wei; JIN Chun-fang; LI Yu-chun; WANG Feng (浙江大学学报. 农业与生命科学版)
The nucleotide sequence and single-strand conformation polymorphism (SSCP) in exon 11 of luteinizing hormone receptor (LHR) gene were studied in Hu sheep (sexual precocity and high prolificacy breeds), Jinzhong sheep and Lingchuan semi-fine wool sheep (delayed puberty and low prolificacy breeds), as well as the effect of the gene polymorphism on the sexual precocity and prolificacy in Hu sheep. Results showed that products amplified by primer P2 and P6 had polymorphisms. Only two genotypes (LL and LM) were found for primer P2, and six SSCP types and three mutations (T2053A, A2044T and G2003A) were detected for primer P6. There were no significant difference in genotype distribution between Hu sheep and Jinzhong sheep but extremely significant differences between Lingchuan semi-fine wool sheep and the other two breeds for primer P2. The distribution of SSCP types and genotypes in three mutation sites (2 053, 2 044 and 2 003) was no significant differences between Hu sheep and Jinzhong sheep but significant difference between Lingchuan semi-fine wool sheep and the other two for primer P6. The allele frequencies of mutation sites, except P2 and 2 003 mutation site of P6 in Lingchuan semi-fine wool sheep, were accordant with Hardy-Weinberg law. Considering that litter sizes among all kinds of genotypes in Hu sheep had no significant difference, it could be preliminarily concluded that exon 11 of LHR had no significant influence on its sexual precocity and prolificacy.